English as a Foreign Language (EFL) teachers teach English for deaf students - Putri Yunisari; Usman Kasim; Saiful Marhaban (Universitas Syiah Kuala, 2021)
This research is motivated by the fact that deaf students have the samerights to get education and access to learn English. However, they needsupport and specific accommodation designs according to their abilities.Teaching English to deaf students is still a problem and varies based onthe situation. Therefore, this research aims at describing how Englishteachers teach deaf students, what problems teachers face in teachingEnglish for deaf students, and the strategies they use. The method usedin this research was qualitative, while the subject was English teachers.The instruments used to collect the data for this research wereobservation, interview and documentation. Besides, the data wereanalyzed using the qualitative data analysis procedures by Yin (2011).The results indicated that there were several problems faced by EFLteachers in teaching the deaf students. It can be categorized into linguisticand nonlinguistic. Likewise, each strategy is implemented based on theproblems and depends on the teachers’ teaching experiences. It issuggested to provide an extensive training program for English teachersand facilitate the learning media to get the success of teaching andlearning process for the deaf students.